Resíduos sólidos e educação ambiental : possibilidade de vivenciar uma sequência de ensino investigativa - Neves, Rosiney Silva (2022)
The problem of this research arose from the fact that I have observed throughout my teaching career, the difficulties of students in changing behaviors and attitudes related to socioenvironmental issues, mainly, the inadequate disposal of solid waste in the environment. Thus, the present research sought to answer the following question: What contributions can the Investigative Teaching Sequence (SEI) approach provide students in understanding the theme Solid Waste as a factor in understanding the transformations of matter? Therefore, the general objective of the research was to build and experience ways to develop the Scientific Literacy of Elementary School students, from the perspective of Environmental Education. The research approach was qualitative in nature with participatory characteristics and was applied in the first half of 2021, online, in a 9th grade elementary school class of a public school in Várzea GrandeMT. The research subjects were 7 students, aged between 14 and 15 years and predominantly female. For data collection, semi-structured questionnaires (IQ and QF), problematizing questions and a logbook were used, which allowed the identification of the subjects' perceptions on the topic addressed and the research problem to be investigated. The research results showed, at different times, the students' conceptions intrinsic to Environmental Education, however, we found that most still have a Romantic-naive Perception about the environmental issue. We believe that the objectives pursued in the research were achieved, considering that the proposed activities allowed to sensitize students about the importance of discussions related to solid waste from the perspective of EE. In this way, SEI contributed to the improvement of students' learning, as they were able to relate the scientific concepts studied in science classes with facts present in their daily lives, thus developing Scientific Literacy. These results enabled the consolidation of the SEI teaching sequence proposal, which was well evaluated by both the research participants and the teachers who validated the Educational Product. However, we recognize that the application of SEI, in fully online classes, had its limitations and made interaction between teacher and students and between students difficult. As well as the development of practical classes.